PROSPECTS FOR GLOBAL VEGETABLE OIL TRADE (British Journal of Global Ecology and Sustainable Development, 2024)
The article provides an overview of the global turnover of trade in vegetable oils. In particular, a statistical analysis of sales volumes of soybean and vegetable oil was performed. According to the author, humanity is now able to drastically reduce pollution by producing vegetable oil and create a world free from harmful gases in the future. This requires increasing the production of vegetable oils, expanding the range of oilseed plants, increasing its productivity through innovative ways.